Changes in attachment dimensions during the treatment of acute post-traumatic stress disorder in sexually assaulted Brazilian women - Maciel, Mariana Rangel; Calsavara, Vinicius Fernando; Zylberstajn, Cecilia; Mello, Marcelo Feijo; Coimbra, Bruno Messina; Mello, Andrea Feijo (Frontiers in Psychology, 2023)
Attachment patterns are established during early childhood; however, extreme experiences throughout life may change this structure, either towards attachment security or insecurity. We analyzed changes in attachment dimensions in women with acute post-traumatic stress disorder (PTSD) following sexual assault, that were randomized to a 14-week treatment with either the medication sertraline or Interpersonal Psychotherapy. Seventy-four adult women who presented significant reduction in PTSD symptoms across the trial responded to the Revised Adult Attachment Scale at baseline, on week 8 of treatment, and at the end of the trial, on week 14. We fitted a generalized linear model to explain the attachment anxiety and avoidance scores at baseline. A generalized linear mixed model investigated how attachment dimensions changed over time. Socioeconomic data, treatment type, history of childhood trauma, and PTSD severity over the 14week period were the considered covariates. At baseline, attachment anxiety was associated with a history of early trauma. Attachment anxiety remained stable during the follow-up. Attachment avoidance, on the other hand, significantly increased from baseline to week 14. Higher avoidance was observed in patients with higher total PTSD scores and on the cluster of hyperarousal symptoms. Races other than White (Black, mixed-race, or Asian) and younger age were associated with higher attachment avoidance. Contrary to our expectations, attachment avoidance increased during follow-up, indicating changes in the interpersonal realm beyond the symptoms of PTSD.